Domestic cats (Felis catus) in Denmark have increased significantly in size since the Viking Age - Bitz-Thorsen, Julie; Gotfredsen, Anne Birgitte (Danish Journal of Archaeology, 2018)
The earliest finds of domestic cat in Denmark date back to the Roman Iron Age (c. 1–375 AD). Initially, cats occurred sparsely and only from the Viking Age (c. 850–1050 AD) did they become more frequent in numbers, though primarily in urban contexts and in connection with fur production. In medieval times, cats became beasts of pest control in rural settlements, manorial estates as well as in the expanding towns, where large and numerous refuse heaps attracted various rodents. To investigate size trends over time of the domestic cat (Felis catus) in Denmark, bone measurements and statistical analyses were performed on archaeological and modern material. Domestic cats were found to increase significantly in size over time since the Viking Age. Limb bones and mandibles exhibited the most significant change in increase (up to 16%), as compared to modern female cats, and tooth size the least (c. 5.5%). The most plausible explanations for such a size increase were improved living conditions caused by increased food availability and a possible shift in human usage of the cats, from a rat and mice captor to a well-fed and well-cared pet. Despite the observed increase in size, domestic cats have kept many osteological features indistinguishable from their wild progenitor.